Social animal bites in a non social way: A profile of human bite cases at GIMS, Kalaburagi (H-K region) - Sangamesh B. Tondare; Shradha S. Maka; Ravindra Chimkode; Mahesh B. Tondare; E.R. Ashish (Al Ameen Medical College, 2018)
Background: Human bites in human beings are important injuries that constitute one of the emergency visits to the General surgery department. Human bite injuries may lead to infection, loss of function, and interpersonal relation. Human bites are usually under reported when they are between intimate partners and are reported due to assault by the biter or accidental injury. Infection and tissue damage make the management of human bites a challenge. Proper documentation and follow up is essential to prevent untoward complications. Aims and Objectives: The study was done to evaluate patients with regards to sex, clinical presentation, site, management and follow up. Materials and Methods: It is a prospective study carried out by department of General surgery at our institute for a period of 1 year. Patients were selected after taking history and examination. The patients were treated by conservative or surgical methods. The outcome and follow up was monitored. Result: The majority of the patients were males as victims and biter also as males. Human bites were common on upper limbs. Most of the patients were medico-legal cases treated by medical management but the follow up was very poor. Conclusion: Most of the patients are medico-legal cases with history of assault and human bite. Majority can be treated by medical management. With the availability of better facilities blood investigations, admission and surgical debridement should be done when there is complete breach of skin. Complications are minimal with surgical expertise.